Preparation method and application of composite nanoparticles with gold-silver core-shell structure
By replacing halogen-containing gold salts with thiourea alloy and combining microwave and ultraviolet radiation technology, the problems of silver halide precipitation and silver etching in the synthesis of gold-shell silver core nanoparticles are solved, and the composite nanometers of gold-silver core-shell structures are realized The uniform growth and structural stability of particles are suitable for applications such as immunoassays.
Patent Information
- Application Number
- CN202411561501.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-21
AI Technical Summary
In the existing methods for synthesizing gold-shell silver core nanoparticles, halogen-containing reagents will lead to silver halide precipitation and silver nanoparticle etching, hindering the uniform growth of gold on the surface of the silver core, and it is difficult to obtain core-shell structural nanoparticles with stable structures.
Thiourea alloy is used to replace halogen-containing gold salts such as tetrachloroalloy acid, and control the reaction conditions through technical means such as microwave radiation and ultraviolet radiation to avoid silver halide precipitation and silver etching to achieve uniformity of gold shell silver core nanoparticles Grow.
The problems of silver halide precipitation and silver etching are effectively avoided, and the uniform and stable growth of gold on the surface of the silver core is achieved, and the composite nanoparticles with uniform and continuous packaging and stable structure are obtained, which are suitable for immunoassay and other applications.
Smart Images

Figure CN119489189A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of gold-silver core-shell structure composite nanoparticles, belonging to the field of nanomaterials. Background Art
[0002] Gold and silver core-shell structured nanoparticles have special physical and chemical properties and have great application prospects in optical biosensing, biomedical diagnosis, surface enhanced Raman scattering, etc.
[0003] The existing method for synthesizing gold-shell silver-core nanoparticles is usually chemical reduction. In the process of chemical reduction, the gold salt generally used is a common reagent such as tetrachlorohydric acid. However, these halogen-containing reagents will cause silver halide precipitation during the synthesis process, which will hinder the attachment and growth of gold on the surface of the silver core; on the other hand, reagents such as tetrachlorohydric acid will cause the silver nanoparticles to be severely etched during the process.
[0004] In short, how to make gold grow evenly and stably on the surface of the silver core epitaxially, avoid silver being etched in the process, and prevent the precipitation of silver halide that hinders surface attachment and growth, so as to obtain core-shell structured nanoparticles with uniform, continuous and stable coating, is a difficult problem in practice. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing gold-silver core-shell structure composite nanoparticles to overcome the problems existing in the above-mentioned prior art.
[0006] The technical solution of the present invention is:
[0007] On the one hand, a method for preparing gold-silver core-shell structure composite nanoparticles is proposed, the method comprising:
[0008] Step 1, prepare a thiourea solution with a concentration of 4-50 g / L, add dilute sulfuric acid, adjust the pH to 1-2, add Fe2(SO4)3 to make the concentration of Fe2(SO4)3 0.2-20 g / L, add 99.99% pure gold at a ratio of 0.02-0.4 g gold per 100 ml solution, heat to 40-50°C, and then add 5% by volume hydrogen peroxide until the gold is dissolved to obtain a gold salt solution;
[0009] Step 2: Use the gold salt solution generated in step 1 to prepare a gold nano seed solution. The specific preparation method is:
[0010] 1) Add ethylene glycol to deionized water, the volume ratio of ethylene glycol to water is 1:20 to 1:5; add PVP, the concentration of PVP is 0.8 to 8 g / L;
[0011] 2) Take the 0.01-0.05M gold salt solution prepared in step 1, and mix it in a volume ratio of 1:300 to 1:
[0012] 1000 ratio is added to the solution prepared in 1);
[0013] 3) Add 0.05-0.5M NaBH4 solution at a volume ratio of 1:5-1:20 under stirring and stir;
[0014] 4) then heating under microwave radiation;
[0015] 5) cooling the solution to room temperature to prepare a gold nanoparticle seed solution;
[0016] Step 3, adding PVP to ionized water, the PVP concentration is 0.8-8 g / L, adding acetonitrile at a volume ratio of 1:1-1:10, adding a 0.1 M ascorbic acid solution at a volume ratio of 1:5-1:20, heating to 40-80° C. in a stirrer, then adding a 0.05-0.3 M silver nitrate solution at a volume ratio of 1:20-1:50, adding the gold nano seed solution generated in step 2 at a volume ratio of 1:100000-1:300000 to obtain an AgNPs solution, centrifuging the AgNPs solution to wash and remove the lower nanolayer;
[0017] Step 4: using the lower nanolayer obtained in step 3 and the gold salt solution generated in step 1 to prepare gold-shell silver-core nanoparticles, the specific preparation method is as follows:
[0018] ① Add deionized water to the lower nanolayer at a volume ratio of 1:5 to 1:50 and stir evenly to obtain an AgNPs colloidal solution;
[0019] ② Add SDS with a concentration of 1-8 g / L to the AgNPs colloidal solution;
[0020] ③ Add the gold salt solution prepared in step 1 to the solution prepared in step ② at a volume ratio of 1:1 to 1:20;
[0021] ④ After 3-5 minutes, add 0.1-0.3M ascorbic acid solution at a volume ratio of 1:10-1:30;
[0022] ⑤ Irradiate with ultraviolet light and stir at the same time to obtain gold shell silver core nanoparticles.
[0023] Preferably, in step 2 (3), the stirring time is 1-5 min and the rotation speed is 1000-1500 r / min.
[0024] Preferably, in step 2 (4), the heating time under microwave radiation is 1-5 min.
[0025] Preferably, the stirrer used in step 3 is a constant temperature magnetic stirrer.
[0026] Preferably, the stirring time of ② in step 4 is 1-5 min, and the rotation speed is 1000-2000 r / min.
[0027] Preferably, the ultraviolet light wavelength in step ② of step 4 is 280-450nm, and the power is 0.07-0.5KW.
[0028] Preferably, the time of irradiating with ultraviolet light and stirring simultaneously in step ② of step 4 is 20-50 min, and the rotation speed is 1000-1500 r / min.
[0029] On the other hand, the application of the gold-silver core-shell structure composite nanoparticles prepared by the method proposed in the first aspect is proposed, and the gold-silver core-shell structure composite nanoparticles are applied to immunoassay.
[0030] The beneficial effects of the present invention are: compared with the prior art,
[0031] 1) The present invention uses thiourea alloy instead of halogen-containing gold salts such as tetrachloroacetic acid, which, on the one hand, avoids the generation of silver halide precipitation during the synthesis process between the gold salt and the silver core, so that gold can be well attached and grown on the surface of the silver core, and the wrapping is uniform and continuous; on the other hand, the electrode potential of the thiourea alloy is relatively low, which makes the reaction process more gentle, slows down the etching of silver nanoparticles during the chemical reduction process, and makes the gold shell silver core nanoparticle structure more stable;
[0032] 2) The present invention first synthesizes large-particle silver nanocores, and silver can grow uniformly and stably to particles with a particle size of 60-110 nm under the action of gold nanoseeds; and uses the excellent affinity of thiourea alloy and silver core to uniformly grow a gold shell on the surface of the silver core, which alleviates the problem of silver being etched during the reduction process, so that gold can further uniformly and stably grow epitaxially on the surface of the silver core, and obtain core-shell structure nanoparticles with uniform and continuous coating and stable structure, so that it can be effectively used in immunoassay;
[0033] 3) Compared with single metal nanoparticles, the gold-silver core-shell composite nanoparticles prepared by the present invention can combine the advantages of materials of different components and have better physical and chemical properties than single metals. Both gold and silver are face-centered cubic metals and have similar lattice parameters, which enables them to be epitaxially grown under appropriate conditions to prepare core-shell gold-silver nanoparticles, so that the obtained particles have the special properties of gold and silver, for example, they have both the stability of gold and the good optical activity of silver;
[0034] 4) The present invention uses gold-shell silver-core nanoparticles instead of colloidal gold. Since nano-scale gold particles are uniformly attached to the surface, they can also be adsorbed by proteins and firmly coated, and further aggregated and colored. The application of gold-shell silver-core nanoparticles in immunoassays can significantly reduce material costs and achieve better color development effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The transmission electron microscope (TEM) images of the core-shell structure composite nanoparticles prepared in the present invention at different magnifications;
[0036] Figure 2 This is a TEM image of the core-shell structure composite nanoparticles prepared by the present invention;
[0037] Figure 3 The core-shell structure composite nanoparticles prepared by the present invention are Figure 2 Energy spectrum analysis diagram of designated area①;
[0038] Figure 4 The core-shell structure composite nanoparticles prepared by the present invention are Figure 2 Energy spectrum analysis diagram of designated area ②;
[0039] Figure 5 This is a comparative test picture of the gold-silver core-shell structure composite nanoparticles prepared by the present invention without concentration and with concentration and direct labeling;
[0040] Figure 6 This is a comparative test picture of the gold-silver core-shell structure composite nanoparticles prepared by the present invention, which were concentrated and washed once with purified water and the 2# reconstituted solution;
[0041] Figure 7 The gold-silver core-shell structure composite nanoparticles prepared by the present invention are tested by using four groups of matching with colloidal gold and latex for comparison. DETAILED DESCRIPTION
[0042] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0043] Implementation Example 1:
[0044] In the process of synthesizing gold and silver core-shell structure nanoparticles by chemical reduction method, large-particle nano can play a better role in labeling some proteins. First, large-particle silver nanocore is synthesized, and silver can grow evenly and stably to particles with a particle size of 60-110nm under the action of gold nanoseed; and the gold shell is evenly grown on the surface of the silver core by the excellent affinity of suitable gold complex and silver core, so that the problem of silver being etched in the process is avoided, and gold can be further evenly and stably epitaxially grown on the surface of the silver core, and the core-shell structure nanoparticles with uniform continuous wrapping and stable structure are obtained, so that it can be effectively used in immunoassay. At the same time, in immunoassay, nanoparticles with larger diameter and larger particles can obtain better labeling and color development effects under certain conditions. The composite nanoparticles synthesized by this method have a particle size of 70-110nm, and have achieved good results in application.
[0045] The invention prepares large-sized gold-silver core-shell structure nanoparticles by chemical method, and successfully applies them to medical immunoassay, achieving good results.
[0046] The experimental steps are as follows:
[0047] 1. Preparation of Gold Salt
[0048] Prepare 4-50g / L thiourea solution, add dilute sulfuric acid, and adjust pH to 1-2. Add Fe2(SO4)3 to a concentration of 0.2-20g / L, add pure gold (99.99%) at a ratio of 0.02-0.4g gold per 100ml solution, heat to 40-50℃, and then add 5% volume concentration of hydrogen peroxide until the gold dissolves to obtain a gold salt solution.
[0049] 2. Preparation of large silver nanoparticles:
[0050] 1) Preparation of gold seeds:
[0051] 1) Add ethylene glycol to deionized water, the volume ratio of ethylene glycol to water is 1:20 to 1:5; add polyvinyl pyrrolidone (PVP), the concentration of PVP is 0.8 to 8 g / L.
[0052] 2) Take the gold salt solution (0.01-0.05M) prepared in step 1 and add it to the solution prepared in step 1) at a volume ratio of 1:300 to 1:1000.
[0053] 3) Add 0.05-0.5M NaBH4 solution at a volume ratio of 1:5-1:20 while stirring, stir for 1-5 minutes, and rotate at 1000-1500 r / min.
[0054] 4) Then heat under microwave irradiation for 1-5 minutes.
[0055] 5) Cool the above solution to room temperature.
[0056] A gold nanoparticle seed solution was prepared.
[0057] 2) Preparation of silver nanoparticles
[0058] PVP is added to ionized water with a PVP concentration of 0.8-8 g / L, acetonitrile is added at a volume ratio of 1:1-1:10, and a 0.1 M ascorbic acid solution is added at a volume ratio of 1:5-1:20. Heat to 40-80°C in a constant temperature magnetic stirrer, then add a 0.05-0.3 M silver nitrate solution at a volume ratio of 1:20-1:50, quickly add the above gold nano seed solution at a volume ratio of 1:100000-1:300000, and stir at 1000-2000 r / min for 10-50 minutes.
[0059] 3. Preparation of Gold Shell Silver Core Nanoparticles
[0060] ① Centrifuge the above AgNPs solution, wash it, remove the lower nanolayer, add deionized water at a volume ratio of 1:5 to 1:50, stir evenly, and obtain a colloidal solution with good light channel transmission when irradiated by a laser pen.
[0061] ② Add sodium dodecyl sulfate (SDS) to the AgNPs colloidal solution, the SDS concentration is 1-8g / L, stir for 1-5min, and the speed is 1000-2000r / min
[0062] ③ Add the gold salt solution (0.001-0.005M) prepared in step 1 at a volume ratio of 1:1 to 1:20
[0063] ④After 3-5 minutes, add 0.1-0.3M ascorbic acid solution at a volume ratio of 1:10-1:30.
[0064] ⑤ Irradiate with ultraviolet light with a wavelength of 280-450nm and a power of 0.07-0.5KW. Continue stirring for 20-50min at 1000-1500r / min
[0065] ⑥ Turn off the UV lamp and stop stirring
[0066] Through the above steps, large-grained gold-silver core-shell structure composite nanoparticles with uniform growth and stable structure are obtained.
[0067] Experimental results:
[0068] The prepared nanoparticles were scanned by transmission electron microscope (TEM) to obtain Figure 1 and Figure 2The results show that compared with the traditional scheme using tetrachloroethylene and gold acid as gold sources, the large-particle gold-silver core-shell structure nanoparticles synthesized by this method are uniform and stable, and the gold atom clusters can evenly attach to the silver core and grow. This is significantly different from the nanoparticles obtained by the traditional method, which are a mixture of gold and silver nanoparticles to a certain extent. The new gold source plays a good role in hindering the attachment of gold and silver cores by silver halide precipitation. The composition analysis of the nanoparticles obtained by this method shows that the mass ratio of the external gold shell of the composite nanoparticles prepared by this method is 15-30%, and the mass ratio of the internal silver core is 70-85%; at the same time, the etching of the silver core in the composite nanoparticles obtained by the traditional method is serious, and this method significantly improves this problem. The electron microscope scanning results show that the silver core is not obviously etched.
[0069] Implementation Example 2:
[0070] In this example, the application of the gold-silver core-shell structure composite nanoparticles prepared by the method proposed in Example 1 is proposed, and the gold-silver core-shell structure composite nanoparticles are applied to immunoassay.
[0071] Experimental results:
[0072] In order to verify that the gold-silver core-shell structure nanoparticles prepared by the present invention have good effects in immunoassay, the following is a comparative experiment conducted by the applicant:
[0073] Experimental report on three kinds of gold and silver particle rapid detection reagents
[0074] 1. Information on reagents and raw materials used:
[0075] Sheep anti-mouse Concentration 5mg / ml Batch number: 20200702 HCG mAb1 Concentration 16.82mg / ml Batch number: HCG21011 HCG mAb2 Concentration 11.26mg / ml Batch number: HCG22502 Colloidal gold particles Nivonos (Suzhou) Bioengineering Co., Ltd. Colloidal gold particles 30nm. latex 300nm latex Gold and silver particles Gold and silver particles ①, gold and silver particles ②, gold and silver particles ③, HCG Yangshen 100mIu / ml、25mIu / ml
[0076] 2. Product Process
[0077] The standard process of Nivonos (Suzhou) Bioengineering Co., Ltd. was used.
[0078] 3. Instruments and Equipment
[0079] JY-EQ03 Continuous film stripping instrument JY-EQ01 Chopping knife-I JY-EQ05 Shell Press JY-EQ02 Centrifuge
[0080] 4. Consumables
[0081] Base Plate 300mm*60mm Absorbent paper 20.6mm Nitrocellulose membrane 120B-20mm Gold-labeled antibody resuspension 2# Gold Rare Gold Label Pad Fiberglass mat Sample pad HCG Pads
[0082] V. Purpose of the experiment
[0083] 1. Use HCG raw materials to verify whether the three types of gold and silver particles can be used for marking
[0084] 2. Comparative sensitivity of the same labeling amount between three kinds of gold and silver particles and colloidal gold and latex
[0085] 6. Set experimental parameters:
[0086] Coating membrane C line: goat anti-mouse concentration is 1.5mg / ml, diluent TBII.
[0087] T line: HCG mAb2, concentration 0.7 mg / ml, 1# coating solution.
[0088] Mark Gold Pad
[0089] (1) Gold and silver particle marking:
[0090] 1. Without concentration, take 1 ml of each sample and label directly:
[0091] Gold and silver particles ①: marking parameters 1: 10:10 speed 11000r*6min 2# gold dilution 100% fixed volume glass fiber pad paving gold Gold and silver particles ②: marking parameters 1: 10:10 speed 11000r*6min 2# gold dilution 100% fixed volume glass fiber pad paving gold Gold and silver particles ③: marking parameters 1: 10:10 speed 11000r*6min 2# gold dilution 100% fixed volume glass fiber pad paving gold 2. Direct marking of gold and silver particles concentration (take 2ml of gold and silver particles):
[0092] Gold and silver particles ①: marking parameters 2: 10:10 speed 11000r*6min 2# gold dilution 50% fixed volume glass fiber mat paved with gold Gold and silver particles ②: marking parameters 2: 10:10 speed 11000r*6min 2# gold dilution 50% fixed volume glass fiber mat paved with gold Gold and silver particles ③: marking parameters 2: 10:10 speed 11000r*6min 2# gold dilution 50% fixed volume glass fiber mat paved with gold 3. Concentrate and wash once, and re-dissolve in purified water (take 2ml of gold and silver particles, centrifuge 11000r*10min to remove the supernatant, and re-dissolve 1ml in pure water)
[0093] Gold and silver particles ①: marking parameters 1: 10:10 speed 11000r*6min 2# gold diluted 100% fixed volume glass fiber mat paved with gold Gold and silver particles ②: marking parameters 1: 10:10 speed 11000r*6min 2# gold diluted 100% fixed volume glass fiber mat paved with gold Gold and silver particles ③: marking parameters 1: 10:10 speed 11000r*6min 2# gold diluted 100% fixed volume glass fiber mat paved with gold 4. Concentrate and wash once, 2# re-dissolve (take 2ml gold and silver particles, centrifuge 11000r*10min to remove the supernatant, 2# re-dissolve 1ml)
[0094] Gold and silver particles ①: Marking parameters 1: 10: 10 Speed 11000r*6min 2# gold dilution 100% constant volume glass fiber pad gold
[0095] Gold and silver particles②: Marking parameters 1:10:10 Speed 11000r*6min 2# gold dilution 100% constant volume glass fiber pad gold
[0096] Gold and silver particles ③: marking parameters 1:10:10 speed 11000r*6min 2# gold dilution 100% constant volume glass fiber pad gold
[0097] (II) Colloidal gold labeling: Colloidal gold particles (30 nm): Labeling parameters 1:10:10 Speed 11000r*6min 100% constant volume glass fiber pad with gold
[0098] (III) Latex marking:
[0099] 300nm latex: marking parameters 10ug / root 2# gold thin glass fiber pad with gold
[0100] Composite: coating membrane (C line sheep anti-mouse 1.5mg / ml T line: HCG mAb2, concentration 0.7mg / ml) matched with the above groups of gold pads respectively
[0101] Sample pad: HCG pad
[0102] Test HCG Yang Shen: 100mIu / ml, 25mIu / ml, 0.01M / LPBS, 0.9% NaCl, 15min results as follows Figure 5 and 6 .
[0103] Figure 5 Test results:
[0104] 1. Unconcentrated gold and silver particles ② and ③ showed obvious color development in the test of Yangshen 100mIu / ml and 25mIu / ml, but no color development was observed in 0.01M / LPBS and 0.9%NaCl.
[0105] 2. Unconcentrated gold and silver particles ① and concentrated gold and silver particles ③ showed color when tested with 100mIu / ml and 25mIu / ml of Yangshen, but no color was shown in 0.01M / LPBS and 0.9% NaCl.
[0106] 3. The concentrated gold and silver particles ① and ② showed a weak color when tested with 100mIu / ml of Yangshen, but no color at 25mIu / ml. Neither 0.01M / LPBS nor 0.9% NaCl showed any color.
[0107] 4. The color ranking of gold and silver particles: unconcentrated gold and silver particles ②> unconcentrated gold and silver particles ③> concentrated gold and silver particles ③> unconcentrated gold and silver particles ①> concentrated gold and silver particles ① and ②.
[0108] Figure 6 Test results:
[0109] 1. Concentrated washing pure water was used to re-dissolve the gold and silver particles ① and ③. The test results showed that the Yang Shen 100mIu / ml showed color, but 25mIu / ml did not show color. 0.01M / LPBS 0.9% NaCl did not show color either;
[0110] 2. Concentrate and wash the gold and silver particles with pure water and re-dissolve them. ② Test Yang Shen 100mIu / ml, 25mIu / ml, 0.01M / LPBS, 0.9% NaCl, and the C line and T line are not colored;
[0111] 3. Concentrated washing 2# complex solution gold and silver particles ①②③ tested Yang Shen 100mIu / ml, 25mIu / ml, 0.01M / LPBS, 0.9% NaCl, and the C line and T line did not show color.
[0112] 4. The order of color development after concentrated washing and adding re-dissolving solution of gold and silver particles: concentrated washing pure water re-dissolving gold and silver particles ①>concentrated washing pure water re-dissolving gold and silver particles ③>concentrated washing pure water re-dissolving gold and silver particles ②, concentrated washing 2# re-dissolving solution gold and silver particles ①②③
[0113] 5. After testing Yang Shen 100mIu / ml and 25mIu / ml, the gold and silver particles were concentrated and washed and then re-dissolved in pure water, and the color was slightly darker than the 2# re-solution.
[0114] Summary: 1. When testing Yangshen 100mIu / ml and 25mIu / ml, the unconcentrated gold and silver particles were darker than the concentrated gold and silver particles. 2. The four groups with darker matching colors are: unconcentrated gold and silver particles ①②③ and concentrated gold and silver particles ③.
[0115] Figure 7 To compare the above four groups of darker colors with colloidal gold and latex test pictures:
[0116] Test results:
[0117] 1. Test Yangshen 100mIu / ml, 25mIu / ml: Unconcentrated gold and silver particles ② have the darkest color, and unconcentrated gold and silver particles ③ are basically consistent with the color of latex; concentrated directly labeled gold and silver particles ③ are a little darker than unconcentrated gold and silver particles ① and colloidal gold.
[0118] 2. Six groups of matching tests: 0.01M / L PBS, 0.9% NaCl, no color was shown
[0119] Summary: 1. Unconcentrated gold and silver particles ①②③ and concentrated gold and silver particles ③ can both label HCG raw materials. 2. Sensitivity ranking: Unconcentrated gold and silver particles ②>Unconcentrated gold and silver particles ③, latex>Concentrated direct labeling gold and silver particles ③>Unconcentrated gold and silver particles ①, colloidal gold.
[0120] VII. Summary:
[0121] 1. Test Yang Shen 100mIu / ml, 25mIu / ml: Unconcentrated gold and silver particles are darker than concentrated gold and silver particles, concentrated washing pure water resolubilization three gold and silver particles ①③ weak color, gold and silver particles ② are not colored; 0.01M / LPBS, 0.9% NaCl, T is not colored; concentrated washing pure water resolubilization gold and silver particles ② and concentrated washing 2# resolubilization gold and silver particles ①②③, C, T lines are not colored
[0122] 2. Both unconcentrated gold and silver particles ①②③ and concentrated gold and silver particles ③ can be used to mark HCG raw materials.
[0123] 3. Under the same conditions, the overall color of the unconcentrated gold and silver particles ② is the darkest, followed by the unconcentrated gold and silver particles ③, and the unconcentrated gold and silver particles ① are the weakest.
[0124] 4. Sensitivity ranking: unconcentrated gold and silver particles ②> unconcentrated gold and silver particles ③, latex> concentrated directly labeled gold and silver particles ③> unconcentrated gold and silver particles ①, colloidal gold.
[0125] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing gold-silver core-shell structure composite nanoparticles, characterized in that: The method is: Step 1, prepare a thiourea solution with a concentration of 4-50 g / L, add dilute sulfuric acid, adjust the pH to 1-2, add Fe2(SO4)3 to make the concentration of Fe2(SO4)3 0.2-20 g / L, add 99.99% pure gold at a ratio of 0.02-0.4 g gold per 100 ml solution, heat to 40-50°C, and then add 5% by volume hydrogen peroxide until the gold is dissolved to obtain a gold salt solution; Step 2: Use the gold salt solution generated in step 1 to prepare a gold nano seed solution. The specific preparation method is: 1) Add ethylene glycol to deionized water, the volume ratio of ethylene glycol to water is 1:20 to 1:5; add PVP, The concentration of PVP is 0.8-8 g / L; 2) Take the gold salt solution with a concentration of 0.01-0.05M prepared in step 1 and add it to the solution prepared in step 1) at a volume ratio of 1:300 to 1:1000; 3) Add 0.05-0.5M NaBH4 solution at a volume ratio of 1:5-1:20 under stirring and stir; 4) then heating under microwave radiation; 5) cooling the solution to room temperature to prepare a gold nanoparticle seed solution; Step 3, adding PVP to ionized water, the PVP concentration is 0.8-8 g / L, adding acetonitrile at a volume ratio of 1:1-1:10, adding a 0.1 M ascorbic acid solution at a volume ratio of 1:5-1:20, heating to 40-80° C. in a stirrer, then adding a 0.05-0.3 M silver nitrate solution at a volume ratio of 1:20-1:50, adding the gold nano seed solution generated in step 2 at a volume ratio of 1:100000-1:300000 to obtain an AgNPs solution, centrifuging the AgNPs solution to wash and remove the lower nanolayer; Step 4: using the lower nanolayer obtained in step 3 and the gold salt solution generated in step 1 to prepare gold-shell silver-core nanoparticles, the specific preparation method is as follows: ① Add deionized water to the lower nanolayer at a volume ratio of 1:5 to 1:50 and stir evenly to obtain an AgNPs colloidal solution; ② Add SDS with a concentration of 1-8 g / L to the AgNPs colloidal solution; ③ Add the gold salt solution prepared in step 1 to the solution prepared in step ② at a volume ratio of 1:1 to 1:20; ④ After 3-5 minutes, add 0.1-0.3M ascorbic acid solution at a volume ratio of 1:10-1:30; ⑤ Irradiate with ultraviolet light and stir at the same time to obtain gold shell silver core nanoparticles.
2. The method for preparing gold-silver core-shell structure composite nanoparticles according to claim 1, characterized in that: In step 2 (3), the stirring time is 1-5 min and the rotation speed is 1000-1500 r / min.
3. The method for preparing gold-silver core-shell structure composite nanoparticles according to claim 1, characterized in that: In step 2 (4), the heating time under microwave radiation is 1-5 min.
4. The method for preparing gold-silver core-shell structure composite nanoparticles according to claim 1, characterized in that: The stirrer used in step 3 is a constant temperature magnetic stirrer.
5. The method for preparing gold-silver core-shell structure composite nanoparticles according to claim 1, characterized in that: The stirring time of ② in step 4 is 1-5min, and the rotation speed is 1000-2000r / min.
6. The method for preparing gold-silver core-shell structure composite nanoparticles according to claim 1, characterized in that: The wavelength of the ultraviolet light in step ② of step 4 is 280-450nm, and the power is 0.07-0.5KW.
7. The method for preparing gold-silver core-shell structure composite nanoparticles according to claim 1, characterized in that: The time of ② in step 4 for irradiating with ultraviolet light and stirring simultaneously is 20-50 min, and the rotation speed is 1000-1500 r / min.
8. An application of gold-silver core-shell structure composite nanoparticles prepared by the method of claims 1-7, characterized in that: The gold-silver core-shell structure composite nanoparticles are applied to immunoassay.
Citation Information
Patent Citations
Method for preparing core-shell gold nanoparticles and detecting concentration of silver ions
CN101927345A
Hollow core-shell nanoparticle and preparation method, test strip and test method
CN108088994A
Au@Ag core-shell nanoparticle loaded silicon nanowire array, preparation method and applications thereof
CN111017871A
Nano particles with gold / silver / gold core-shell structure and synthesis method of nano particles
CN113059177A
Synthetic method of gold-shell silver-core nanoparticles
CN116475426A
Cited By
Synthetic method of gold-shell silver-core nanoparticles
CN116475426A
A method for synthesizing gold shell-silver core nanoparticles
CN116475426B